Linearly polarised organic light-emitting diodes (OLEDs): synthesis and characterisation of a novel hole-transporting photoalignment copolymer - Aldred, M.P.; Vlachos, P.; Contoret, A.E.A.; Farrar, S.R.; Chung-Tsoi, W.; Mansoor, B.; Woon, K.L.; Hudson, R.; Kelly, S.M.; O'Neill, M. (Royal Society of Chemistry, 2005)
We describe the synthesis and characterisation of a novel hole transporting photoalignment copolymer for linearly polarised emission. The copolymer has a coumarin side-chain which undergoes (2 + 2) cycloaddition on irradiation with ultraviolet light. A fluorene side-chain, whose ionisation potential is well matched to the work-function of indium tin oxide, provides hole transporting properties. Polarised green electroluminescence was obtained by spin coating a novel polymerisable and light-emitting liquid crystal onto the photoaligned copolymer. A polarisation ratio value of 13 : 1 and a polarised irradiance of 200 cd m−2 was obtained at 9 V. Polarised red emission is also described in a guest–host configuration. The spatial patterning of the polarisation direction is also shown.